Exploring Nurses' Attitudes, Skills, and Beliefs of Medication Safety Practices. Issue 4 (8th October 2022) - Arkin, Laura; Schuermann, Andrea; Penoyer, Daleen; Loerzel, Victoria
Abstract : Background: Medication errors exist within health care systems despite efforts to reduce their incidence. These errors may result in patient harm including morbidity, mortality, and increased health care costs. Purpose: The purpose of this study was to explore direct care nurses' attitudes, skills, and beliefs about medication safety practice. Methods: Researchers conducted a descriptive exploratory study using the Nurses' Attitudes and Skills around Updated Safety Concepts (NASUS) scale and the Nurse Beliefs about Errors Questionnaire (NBEQ). Results: Responses from 191 surveys were analyzed. Of the participants, 70% were bachelor's prepared registered nurses and 88% were female. Results of the NASUS scale revealed the median of means of the Perceived Skills subscale was 79.2 out of 100 and the Attitudes subscale was 65.8 out of 100. The mean of the belief questions related to severity of error was 7.66 out of 10; most participants agreed with reporting of severe errors, reporting errors with moderate or major adverse events, and reporting of incorrect intravenous fluids. Conclusions: Understanding direct care nurses' attitudes, skills, and beliefs about medication safety practices provides a foundation for development of improvement strategies.